2001
DOI: 10.1161/hc3701.096099
|View full text |Cite
|
Sign up to set email alerts
|

A 30-Year Follow-Up of the Dallas Bed Rest and Training Study

Abstract: Background-Aerobic power declines with age. The degree to which this decline is reversible remains unclear. In a 30-year longitudinal follow-up study, the cardiovascular adaptations to exercise training in 5 middle-aged men previously trained in 1966 were evaluated to assess the degree to which the age-associated decline in aerobic power is attributable to deconditioning and to gain insight into the specific mechanisms involved. Methods and Results-The cardiovascular response to acute submaximal and maximal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(94 citation statements)
references
References 46 publications
(69 reference statements)
8
76
2
1
Order By: Relevance
“…Specifically, the typically lower initial baseline VO 2max in the old subjects mathematically biases this assessment of improvement in favor of the older subjects. Therefore, previous studies have indeed revealed robust improvements in VO 2max , presented as a percentage change, of 10-30 % in older subjects after training interventions lasting between 8 weeks and 1 year (Coggan et al 1992;Fujimoto et al 2010;Kohrt et al 1991;Makrides et al 1990;McGuire et al 2001b;Murias et al 2010;Osteras et al 2005). These percentage improvements in VO 2max are comparable, if not even higher than the improvements sometimes documented in young subjects Makrides et al 1990;Murias et al 2010).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Specifically, the typically lower initial baseline VO 2max in the old subjects mathematically biases this assessment of improvement in favor of the older subjects. Therefore, previous studies have indeed revealed robust improvements in VO 2max , presented as a percentage change, of 10-30 % in older subjects after training interventions lasting between 8 weeks and 1 year (Coggan et al 1992;Fujimoto et al 2010;Kohrt et al 1991;Makrides et al 1990;McGuire et al 2001b;Murias et al 2010;Osteras et al 2005). These percentage improvements in VO 2max are comparable, if not even higher than the improvements sometimes documented in young subjects Makrides et al 1990;Murias et al 2010).…”
Section: Discussionmentioning
confidence: 78%
“…Typically, maximal oxygen consumption (VO 2max ) falls steadily from 35 to 40 years of age at a rate of ∼10 % per decade (Fleg et al 2005;Hawkins and Wiswell 2003;McGuire et al 2001a;Ogawa et al 1992;Tanaka and Seals 2008). Although this decline in aerobic capacity with increasing age is often considered to be inevitable, it seems that this fall can be decelerated, maintained, or even reversed in the elderly by maintaining a high level of physical activity (Faulkner et al 2008;Fujimoto et al 2010;Grimsmo et al 2010;Heath et al 1981;McGuire et al 2001b;Murias et al 2010;Osteras et al 2005;Posner et al 1986;Rogers et al 1990;Trappe et al 2013;Trappe et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, mitochondrial partial dysfunction occurs due to unmatched or perhaps intrinsic mitochondrial function and regulation (abnormal mitochondrial function) and hence the inability of skeletal muscles to fully extract oxygen from the arterial blood due to considerably reduced normal oxygen conductance from the muscle capillary to the mitochondria [44]. The latter is most likely associated with a poor muscle microcirculatory network and capillarymyofiber dissociation [43]. The molecular defect in subjects with mitochondrial myopathies commonly involves the mitochondrial genome, with the detection of either single large-scale deletions or point mutations [46].…”
Section: Aging Considerationsmentioning
confidence: 99%
“…Inactivity reduces muscular strength and physical function (McGuire et al 2001, Suesada et al 2007, Kortebein et al 2008), and muscular strength decreases substantially in the first week after total hip arthroplasty (THA) (Holm et al 2013). Early recovery and rehabilitation of the weakened musculature is therefore of importance (Sicard-Rosenbaum et al 2002).…”
mentioning
confidence: 99%